Normal human enthesis harbours conventional CD4+ and CD8+ T cells with regulatory features and inducible IL-17A and TNF expression. Issue 8 (13th May 2020) - Watad, Abdulla; Rowe, Hannah; Russell, Tobias; Zhou, Qiao; Anderson, Lisa K; Khan, Almas; Dunsmuir, Robert; Loughenbury, Peter; Borse, Vishal; Rao, Abhay; Millner, Peter A; Bragazzi, Nicola Luigi; et al.
Abstract : Background: The human enthesis conventional T cells are poorly characterised. Objectives: To study the biology of the conventional T cells in human enthesis. Methods: CD4+ and CD8+ T cells were investigated in 25 enthesis samples using immunofluorescence, cytometrically, bulk RNAseq and quantitative real-time PCR following anti-CD3/CD28 bead stimulation to determine interleukin (IL)-17A and tumour necrosis factor (TNF) levels. T-cell receptor (TCR) repertoires were characterised and a search for putative T-cell reactivity was carried out using TCR3 database. The impact of pharmacological antagonism with retinoic acid receptor-related orphan nuclear receptor gamma t inhibitor (RORγti), methotrexate and phosphodiesterase type 4 inhibitor (PDE4i) was investigated. Results: Immunofluorescence and cytometry suggested entheseal resident CD4+ and CD8+ T cells with a resident memory phenotype (CD69+/CD45RA-) and tissue residency gene transcripts (higher NR4A1/AhR and lower KLF2/T-bet transcripts). Both CD4+ and CD8+ T cells showed increased expression of immunomodulatory genes including IL-10 and TGF-β compared with peripheral blood T cells with entheseal CD8+ T cells having higher CD103, CD49a and lower SIPR1 transcript that matched CD4+ T cells. Following stimulation, CD4+ T cells produced more TNF than CD8+ T cells and IL-17A was produced exclusively by CD4+ T cells. RNAseq suggested both Cytomegalovirus and influenza A virus entheseal resident T-cell clonotype reactivity. TNF and IL-17A production from CD4+ T cells was effectively inhibited by PDE4i, while RORγti only reduced IL-17A secretion. Conclusions: Healthy human entheseal CD4+ and CD8+ T cells exhibit regulatory characteristics and are predicted to exhibit antiviral reactivity with CD8+ T cells expressing higher levels of transcripts suggestive of tissue residency. Inducible IL-17A and TNF production can be robustly inhibited in vitro.